Pengaruh Transaksi Internet Banking, Mobile Banking, dan Fee Based Income Terhadap Profitabilitas Pada Bank Umum Konvensional - Rizqi Safitri Zahira; Oryza Tannar (Al-Buhuts, 2025)
This study aims to determine the effect of internet banking transactions, mobile banking transactions, and fee-based income on profitability at Conventional Commercial Banks in 2019-2022. This type of research uses a quantitative approach. In addition, the type and source of data is secondary data with sampling techniques using purposive sampling. The results of the sampling amounted to 60 annual reports from 15 conventional commercial banks listed on the IDX in 2019-2022 which were obtained through the official website of each bank and the Indonesia Stock Exchange website. The data collection technique uses the documentation method in the form of annual reports or annual reports and the data analysis uses the panel data regression equation. The results obtained by this study are (1) internet banking transactions have no effect on profitability (ROA) with a significance of 0.1536> 0.05, (2) mobile banking transactions also have no effect on profitability (ROA) with a significance of 0.3973> 0.05, (3) fee-based income has a significant negative effect on profitability (ROA) with a significance of 0.0086 <0.05.